Initial Testing (Stage 1) of MK‐8242—A Novel MDM2 Inhibitor—by the Pediatric Preclinical Testing Program. Issue 10 (30th May 2016) - Kang, Min H.; Reynolds, C. Patrick; Kolb, E. Anders; Gorlick, Richard; Carol, Hernan; Lock, Richard; Keir, Stephen T.; Maris, John M.; Wu, Jianwrong; Lyalin, Dmitry; Kurmasheva, Raushan T.; Houghton, Peter J.; et al.
Abstract : Background: MK‐8242 is an inhibitor of MDM2 that stabilizes the tumor suppressor TP53 and induces growth arrest or apoptosis downstream of TP53 induction. Procedures: MK‐8242 was tested against the Pediatric Preclinical Testing Program (PPTP) in vitro cell line panel at concentrations from 1.0 nM to 10.0 μM and against the PPTP in vivo xenograft panels using oral gavage on Days 1–5 and Day 15–19 at a dose of 125 mg/kg (solid tumors) or 75 mg/kg (acute lymphoblastic leukemia [ALL] models). Results: The median IC50 for MK‐8242 was 0.07 μM for TP53 wild‐type cell lines versus >10 μM for TP53 mutant cell lines. MK‐8242 induced a twofold or greater delay in time to event in 10 of 17 (59%) of TP53 wild‐type solid tumor xenografts, excluding osteosarcoma xenografts that have very low TP53 expression. Objective responses were observed in seven solid tumor xenografts representing multiple histotypes. For the systemic‐disease ALL panel, among eight xenografts there were two complete responses (CRs) and six partial responses (PRs). Two additional MLL‐rearranged xenografts (MV4;11 and RS4;11) grown subcutaneously showed maintained CR and PR, respectively. The expected pharmacodynamic responses to TP53 activation were observed in TP53 wild‐type models treated with MK‐8242. Pharmacokinetic analysis showed that MK‐8242 drug exposure in SCID mice appears to exceed that was observed in adult phase 1 trials. Conclusions: MK‐8242‐induced tumor regressions across multiple solid tumor histotypes and induced CRs or PRs for most ALL xenografts. This activity was observed at MK‐8242 drug exposures that appear to exceed those observed in human phase 1 trials.